(untitled) (UUM Journal of Legal Studies, 2022)
Medicine advertisements need to be controlled to ensure public interest is protected from harm and complications. This is because the medicine advertisements accessed could be misleading, untrue, and contain highly exaggerated advertising claims. The law in the control of medicine advertising is complex and advancements in technology has made advertising of medicines even more challenging. Typically, every public-policy problem will be solved through legislation or government action. However, the implementation of the self-regulation approach in regulatory enforcement of medicine advertisements has not been evidently shown and therefore, needs to be studied. This study is aimed at determining regulatees’ initial perception in adopting the self-regulation approach in the regulatory enforcement of medicine advertisements in Malaysia. A mixed method study was conducted using data collected from the feedback obtained through an evaluation form distributed at a seminar organised in 2015 and from library research. Data generated from the 2015 seminar was the only data available at the national level and this data could only be obtained from the Pharmacy Enforcement Division. The seminar, which was attended by regulators, government agencies, publishers, advertising agencies, companies from the pharmaceutical industry, and the relevant organisations who were stakeholders in he industry, was a way to advance new guidelines and a regulatory enforcement approach on medicine advertisement. The results from the survey revealed that 58 percent of the participants favoured the self-regulation approach. Their perceptions were found to be positive towards the self-regulation approach. Based on a thematic analysis, the results seemed to suggest that the concern of the regulatees about the self-regulation approach could be categorised into four important factors, which were the Malaysian industry’s attitude and behaviour, government approval, government enforcement, and the management of the self-regulation approach. Nevertheless, in order to adopt the self-regulation approach, this study has highly recommended that the government should explicitly encourage self-regulatory bodies in Malaysia to implement the self-regulatory approach. For future studies, it is suggested that research be conducted to identify the effectiveness of the self-regulation approach among the various stakeholders of medicine advertisement.